Total Hip Arthroplasties in Polio Survivors: A Systematic Review - Akadiri, Michael; Smith, Christian; Wong, Fabian; Davidson, Jerome (The Journal of Hip Surgery, 2023)
There is a paucity of evidence regarding outcomes of post-polio patients following total hip arthroplasty (THA). This systematic review examines the evidence regarding implant choice, surgical planning, outcomes, and complications for post-polio patients undergoing THA. A multidatabase literature search was performed. Included articles were assessed for methodological quality using the abridged Downs and Black's criteria. Data was extracted regarding patient demographics, intraoperative details, outcome measures, and postoperative complications. Six articles were included in this review; all were retrospective case series. One hundred and six hips in 97 patients underwent THA. There was no consensus regarding the optimal approach or implant fixation. Patient-reported outcome measures (PROMs) showed a demonstrable improvement following THA. Postoperative dislocation was more common compared with patients without post-polio syndrome. Patients with post-polio syndrome who undergo THA have beneficial outcomes as determined by improvements in PROMs. Higher quality research may not be possible due to the increasing rarity of patients suffering from polio.
Keywords: total hip arthroplasty; total hip replacement; polio; poliomyelitis; Harris Hip Score